Biosorption of basic dyes using sewage treatment plant biosolids - Alam, Md. Zahangir (Asian Network For Scientific Information, 2004)
Studies on the removal of three basic dyes (Basic Blue 3, Basic Red 22, Basic Black 9) from aqueous solutions by adsorption on Sewage Treatment Plant (STP) biosolids (sludge) as an adsorbent were carried out with an aim to obtain information on treating effluents from textile and/or dye industries. A series of experiments were undertaken in a batch adsorption technique to access the effect of the process variables i.e. initial dye concentration, contact time, initial pH, adsorbent dose, temperature and agitation rate. The adsorption capacity of basic dyes was higher (22-24 mg gG1) with the lower values of the temperature (25-30°C), adsorbent dosage (0.5-0.75% w/v), higher values of the initial pH (8-9) and agitation rate (150-200 rpm). The equilibrium in the solution was observed within 2 h of operation. The equilibrium isotherm for each dye was determined to describe the biosorption processes. The results showed that the equilibrium data were fitted by both of the Langmuir and Freundlich isotherms while Freundlich isotherms was slightly better fitted for Basic Blue 3 and Langmuir was for the Basic Black 9 in terms of regression coefficients (R2).